Spatial Changes in the Settlement of Panta'nakan Lolo Tourism Village, Kesu District, North Toraja Regency - Sari, Nila Puspita; Giyarsih, Sri Rum; Kurniawan, Andri (Journal of Geosciences and Environmental Studies, 2025)
The tourism sector is growing rapidly and emerging as a key driver of regional development. One approach to fostering tourism is establishing Tourism Villages, such as Panta'nakan Lolo Village, which capitalizes on its tourism potential. As a tourist village, it features iconic attractions like Ke'te Kesu. Tourism development has driven increased accommodations alongside physical and spatial changes in the settlement environment. These include new construction, spatial reorganization, and changes in tourism activities and management. This study examines spatial changes in Panta'nakan Lolo Village's settlements before and after its designation as a Tourism Village. Using a qualitative method, data were collected through field surveys, in-depth interviews, and documentation. Spatial-temporal analysis identified changes in land use patterns during 2012, 2018, and 2024. Additionally, settlement patterns were assessed using the Nearest Neighbor Analysis approach with ArcGIS software. The results reveal significant spatial transformations linked to the village’s tourism development. These changes include expanded built-up areas, integration of tourism elements into settlements, and the rise of tourism-related activities and management systems.